Tindak Tutur Hakim dalam Menangani Perkara Tindak Pidana di Pengadilan Negeri Gorontalo - Fitrawati Abdullah (Pusat riset dan Inovasi Nasional, 2025)
The study titled “Judges’ Speech Acts in Handling Criminal Cases at the Gorontalo District Court” aims to describe the forms, functions, and meanings of speech acts used by judges in leading court sessions. The introduction emphasizes the importance of language in judicial processes to establish effective, fair, and authoritative communication among judges, defendants, prosecutors, and legal counsels. This study employs a descriptive qualitative method with a pragmatic approach. Data were collected through direct observation, documentation, and transcription of court proceedings. The analysis is based on Austin and Searle’s speech act theory, which includes locutionary, illocutionary, and perlocutionary acts. The results show that judges use various types of speech acts, such as directive, declarative, representative, and expressive acts. Illocutionary acts, particularly commands, questions, and assertions, are the most dominant. Their functions are not only to direct the course of the trial but also to maintain order, emphasize legal aspects, and clarify understanding among the parties involved. In conclusion, judges’ speech acts serve as strategic communicative tools with pragmatic power that influence the course of the trial and determine the effectiveness and fairness of the judicial process.